(untitled) (Research, Society and Development, 2022)
This work aimed to extract clove essential oil, using alternative and low-cost materials, in a pandemic period and with remote teaching. For the assembly of the hydrodistiller, materials easily found at home and in the trade were used, such as: PET bottle, aluminum can, level hose, epoxy resin, glass containers, 70º INPM alcohol, cotton, Indian cloves, etc. The extraction of clove essential oil was carried out successfully. At the end of the experiment, a water-oil mixture was obtained. The presence of clove essential oil was confirmed by the characteristic odor. Therefore, when considering the potential of experimentation as a methodology that integrates theory and practice, as well as the remote teaching model adopted during the COVID-19 pandemic, it is evident that experiments with alternative materials constitute a viable option for teaching Chemistry in distance learning situations or in cases of lack of laboratory resources in educational institutions.